Association of psychological and physical health with quality of life in patients with haemophilia: a brief review - Dutta, Himanish; Choudhry, Dimple; Kumar Atri, Sudhir; Sangeeta,; Jhandai, Malika (International Journal of Research in Medical Sciences, 2024)
Hemophilia is an inherited bleeding disorder that is caused by an x-linked deficiency of clotting factors VIII in hemophilia A and IX in hemophilia B. Hemophilia A is more common than hemophilia B accounting for approximately 80-85% of all cases. Patients with hemophilia face several challenges due to bleeding episodes such as chronic arthropathy, functional disabilities, and many other health issues. Consequently, patients with hemophilia experience psychological comorbidities such as depression, anxiety, and social isolation. This emphasizes the importance of addressing both physical and mental health aspects in the overall care of these patients. To determine the association between psychological and physical health with quality of life in patients with hemophilia. This narrative review is conducted on databases from PubMed, Google Scholar, and ResearchGate. This review included 11 studies on the association between psychological and physical health with quality of life in patients with hemophilia. In conclusion, many studies show us different parameters between psychological health and physical health with quality of life in hemophilic patients but there is no research showing us the association between psychological and physical health with quality of life in hemophilic patients.